Analisis Buku Teks Mata Pelajaran Geografi Kelas XI SMA/Sederajat Pada Materi Dinamika Kependudukan di Indonesia untuk Perencanaan Pembangunan - Muhammad Muhammad; Karunia Puji Hastuti; Faisal Arif Setiawan (JPG (Jurnal Pendidikan Geografi), 2021)
According to BSNP in the review of textbooks, there are four aspects of feasibility that must be met. The four aspects are the feasibility of content, presentation, linguistic, and graphics. The purpose of this study is to determine the level of feasibility of content, presentation, linguistic, and graphics on the material that is the focus of research. The focus of this research is a study of the material on Population Dynamics in Indonesia for Development Planning contained in the Geography textbook for class XI SMA/equivalent. The book sampled for this research is Geography Textbook Volume 2 for SMA/MA Class XI Specialization Groups, written by Yasinto Sindhu Priastomo, published by Erlangga. The data were obtained by using documentation techniques, namely analyzing documents in the form of one material from the textbook that became the research sample. The results of the researcher's assessment were reviewed by three reviewers, so that the research results were more valid. The research data were analyzed by descriptive method. The results of the research and discussion can be concluded that the material analyzed is included in the feasible criteria. Based on the aspect of content feasibility, the material studied is included in the feasible criteria with a percentage of 73,11%. The level of presentation feasibility is included in the feasible criteria with a percentage of 79,83%. The level of linguistic feasibility is included in the feasible criteria with a percentage of 80,95%. The level of graphics feasibility is included in the feasible criteria with a percentage of 84,42%.